Individual-level Association of Influenza Infection With Subsequent Pneumonia: A Case-control and Prospective Cohort Study. (27th July 2020) - Kubale, John; Kuan, Guillermina; Gresh, Lionel; Ojeda, Sergio; Schiller, Amy; Sanchez, Nery; Lopez, Roger; Azziz-Baumgartner, Eduardo; Wraith, Steph; Harris, Eva; Balmaseda, Angel; Zelner, Jon; et al.
Abstract: Background: Pneumonia is a leading cause of mortality worldwide. Influenza may result in primary pneumonia or be associated with secondary bacterial pneumonia. While the association with secondary pneumonia has been established ecologically, individual-level evidence remains sparse and the risk period for pneumonia following influenza poorly defined. Methods: We conducted a matched case-control study and a prospective cohort study among Nicaraguan children aged 0–14 years from 2011 through 2018. Physicians diagnosed pneumonia cases based on Integrated Management for Childhood Illness guidelines. Cases were matched with up to 4 controls on age (months) and study week. We fit conditional logistic regression models to assess the association between influenza subtype and subsequent pneumonia development, and a Bayesian nonlinear survival model to estimate pneumonia hazard following influenza. Results: Participants with influenza had greater risk of developing pneumonia in the 30 days following onset compared to those without influenza (matched odds ratio [mOR], 2.7 [95% confidence interval CI, 1.9–3.9]). Odds of developing pneumonia were highest for participants following A(H1N1)pdm09 illness (mOR, 3.7 [95% CI, 2.0–6.9]), followed by influenza B and A(H3N2). Participants' odds of pneumonia following influenza were not constant, showing distinct peaks 0–6 days (mOR, 8.3 [95% CI, 4.8–14.5] days) and 14–20 (mOR, 2.5 [95% CI, 1.1–5.5] days) after influenza infection. Conclusions: Influenza is a significant driver of both primary and secondary pneumonia among children. The presence of distinct periods of elevated pneumonia risk in the 30 days following influenza supports multiple etiological pathways. Abstract : We found a clear, individual-level association between influenza and subsequent pneumonia among Nicaraguan children. The presence of distinct periods of elevated risk is highly suggestive of the existence of different etiologic pathways leading from influenza to pneumonia.